Case study on designing a standard single storey house building plan for Kampung Tebobon Baru / Michelle Majalap Mojiun - Mojiun, Michelle Majalap (Universiti Teknologi Mara, Perak, 2014)
Students studying Diploma in Building Surveying in University Teknologi MARA (UiTM) will undergo industrial training at their last semester (6th Semester in the third year) to gain more experience and knowledge in a working environment. In this report, it explains the experience of the trainee in designing a standard single storey house building plan at a site located at Kampung Tebobon Baru. Construction is important in society as it provides shelter, easy transportation and job opportunities. In Construction Technology it includes The Technology of Construction Management, The Technology of Construction Personnel, The Technology of Construction Materials and Products and The Technology of Construction Processes and Production. In The Technology of Construction Management, it includes designing a project. Designing of building and structures is the act of finding the best way to solve the construction problem. Designing is a process in which the architect or engineer identifies the material and techniques to be used in the construction project. In most cases, design of a building usually is considered by its function, form, cost and material and financing. The design process begins from developing a problem that need to be solved. Then it is followed up with getting ideas, doing some research and development, refinement of ideas, analysis, getting solution to problems, making decisions and lastly implementation. The company chosen by the trainee to undergo her industrial training is at the Kota Kinabalu City Hall, Sabah. The trainee was given a task to design a standard building plan for a single storey house for the Relocation of Kampung Tebobom Baru Project. This design will be a standard guideline to clients who will build a house in Kampung Tebobom Baru. The trainee went through the stages of design beginning from the pre-design stage, design stage and post-design stage. With her experience in design during her studies and also some guidance from the department’s architecture, the trainee is able to complete the design.